1988
DOI: 10.1038/334585a0
|View full text |Cite
|
Sign up to set email alerts
|

Simple RNA enzymes with new and highly specific endoribonuclease activities

Abstract: In vitro mutagenesis of sequences required for the self-catalysed cleavage of a plant virus satellite RNA has allowed definition of an RNA segment with endoribonuclease activity. General rules have been deduced for the design of new RNA enzymes capable of highly specific RNA cleavage, and have been successfully tested against a new target sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
570
0
6

Year Published

1988
1988
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,080 publications
(581 citation statements)
references
References 25 publications
5
570
0
6
Order By: Relevance
“…4,5 It is tary to the target RNA. 11 Recently, ribozymes have been apparent that to target the viruses' highly conserved targeted to a wide variety of substrates and tested in biofunctional protein domains or viral RNA structures for logical systems, to achieve inhibition of cellular gene inhibition of viral replication may require prevention of expression or viral replication. 12 escape mutations, as a key element for long-term theraWith viral RNA as the packaged genetic material, peutic benefit of HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 It is tary to the target RNA. 11 Recently, ribozymes have been apparent that to target the viruses' highly conserved targeted to a wide variety of substrates and tested in biofunctional protein domains or viral RNA structures for logical systems, to achieve inhibition of cellular gene inhibition of viral replication may require prevention of expression or viral replication. 12 escape mutations, as a key element for long-term theraWith viral RNA as the packaged genetic material, peutic benefit of HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Because this cleavage renders an mRNA molecule untranslatable and prone to rapid degradation by intracellular nucleases, ribozyme action abrogates protein expression in a highly specific and effective manner, and ribozymes, eg short hammerhead ribozymes, 4 represent a potentially formidable therapeutic agent to control expression of any gene of interest. However, the use of ribozymes as therapeutic agents involves several issues such as cellular delivery, uptake, and intracellular localization, as well as ribozyme stability, catalytic activity, and toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The discovery that certain RNA species possess catalytic activity has generated significant interest in the potential therapeutic use of catalytic RNA molecules (ribozymes) in controlling gene expression (for a review, see Christoffersen & Marr, 1995)+ Ribozymes have been shown to function in trans and can be directed against foreign target sequences by flanking the catalytic core with sequences complementary to the target (Uhlenbeck, 1987;Haseloff & Gerlach, 1988)+ The hammerhead is the smallest of the known ribozyme motifs and therefore amenable to experimental manipulation (for a review, see Symons, 1992)+ Hammerhead ribozymes have broad potential as therapeutic agents for the selective control of gene expression (for a review, see Haseloff & Gerlach, 1988;Sarver et al+, 1990;Christoffersen & Marr, 1995)+ An important problem confronting the use of hammerhead ribozymes as therapeutic agents is that of maximizing the interaction of ribozymes to their target RNAs in vivo+ Experiments employing the unique property of retroviruses to dimerize prior to and during packaging have provided a paradigm for ribozyme-target colocalization (Sullenger & Cech, 1993;Pal et al+, 1998)+ The dimerization and packaging of retroviral RNAs creates a unique physical association of two genomic RNAs+ When a ribozyme is tethered to the dimerization domain, the physical interaction of two dimerization sequences facilitates the base pairing of ribozyme to target+ Physical associations of nonviral RNAs occur within cells, but these usually involve specific base pairing interactions such as snRNAs with splicing signals (Wu & Manley, 1991;Sun & Manley, 1995;Incorvaia & Padgett, 1998)+ The interaction of U1 snRNA with the 59 splice signal has been used as an approach for colocalization of a ribozyme with an HIV target (Michienzi et al+, 1998)+ More subtle methods for ribozyme-target colocalization can take advantage of the properties of some messenger RNAs to be localized within specific subcellular compartments+ The first evidence for cytoplasmic mRNA localization came from the observation that actin tran-scripts are unevenly distributed in ascidian embryos (Jeffery et al+, 1983)+ Subsequently, several maternal mRNAs were identified in Xenopus (Melton, 1987) and Drosophila (Frigerio et al+, 1986) that are localized during oogenesis, and many mRNAs are localized in neurons (Garner et al+, 1988;Burgin et al+, 1990;Tiedge et al+, 1991) and oligodendrocytes (Ainger et al+, 1993)+ Localized mRNAs have also been discovered in somatic cells …”
Section: Introductionmentioning
confidence: 99%